2020
DOI: 10.5765/jkacap.200022
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-induced Psychosis in Adolescent Patient with Crohn’s Disease

Abstract: Crohn’s disease is a chronic inflammatory disease that involves the upper and lower gastrointestinal tracts, including the oral cavity. For the conventional treatment of inflammatory bowel diseases, steroids are usually used as induction therapy, and azathioprine is used as maintenance therapy. Steroids are associated with various side effects. Under rare circumstances, they can even cause psychotic symptoms, and reports on steroid-induced psychosis in the pediatric population are few. Here, we report the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…[7] Furthermore, Kim et al reported a 16-year-old female patient diagnosed with CD, which showed psychotic changes after 2 weeks of administering prednisolone 60 mg/day, which recovered gradually after 1 week of discontinuation steroid and starting antipsychotic therapy. [8] The consensus guidelines of ECCO/ESPGHAN on the medical management of pediatric CD states that "In children and adolescents who did not have finished their growth, exclusive enteral nutrition is the induction therapy of the first choice due to its excellent safety profile, preferable over corticosteroids, which are equipotential to induce remission." [9] On the same consensus guideline, when prednisolone fails, then budesonide is the 2 nd line.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Furthermore, Kim et al reported a 16-year-old female patient diagnosed with CD, which showed psychotic changes after 2 weeks of administering prednisolone 60 mg/day, which recovered gradually after 1 week of discontinuation steroid and starting antipsychotic therapy. [8] The consensus guidelines of ECCO/ESPGHAN on the medical management of pediatric CD states that "In children and adolescents who did not have finished their growth, exclusive enteral nutrition is the induction therapy of the first choice due to its excellent safety profile, preferable over corticosteroids, which are equipotential to induce remission." [9] On the same consensus guideline, when prednisolone fails, then budesonide is the 2 nd line.…”
Section: Discussionmentioning
confidence: 99%
“…While a population-based cohort study conducted in Taiwan (2020) demonstrated a significant association between schizophrenia and subsequent IBD development (1.14% vs. 0.25% in non-IBD population), other studies failed to demonstrate any association between somatic and mental illnesses [112,113]. In pediatric populations, rare and isolated cases of medication-induced psychosis are described in the literature [114,115] Recent evidence suggests there is a possible association between IBD and eating disorders, although the exact mechanisms involved in its ethio-pathogenesis are not fully understood. This association may lead to worse prognosis [108,116,117].…”
Section: Mental Healthmentioning
confidence: 99%
“…Quetiapine at 300mg/day for 3 months after onset of psychiatric manifestation . Ward et al 16 demonstrates successful management of psychosis with tab. Aripiprazole followed by Inj.…”
Section: Introductionmentioning
confidence: 99%